Influência da calcitonina na regeneração óssea em mandíbulas de ratas ovariectomizadas - Arisawa, Emilia Angela Loschiavo [UNESP] (2000)
In This work we studied the action of calcitonin on bone regeneration in the jaws of normal and ovariectomized rats with and without administration of calcitonin. One hundred rats aged approximately sixty days were used for this study. Of these fifty were ovariectomizedOv forming group and one month after the surgery, animals in all a hundred surgical bone defect was made in the angle of the mandible, creating a bone lesion of approximately 4 mm, covered with a PTFE barrier. OvThe animals were divided into two equal groups: Ov (ovaricctomizados) and LMO (ovariectomized with calcitonin). The other fifty animals, only with the bone lesion were also divided into two groups: control (C) and CM (control with calcitonin). Treated groups received the first dose of the substance immediately after surgery, the dose of 2 IU / kg IM three times per week. The animals were sacrificed after three, seven, 14, 21 and 28 days, with their jaws removed and sent for histological preparation. Densitometric analyzes were performed histological and histomorphometric verifying that it was observed that the Ov animals showed decreased bone density and a much slower regenerative process, when compared with control animals. Calcitonin proved effective in both ovariectomized animals and in those with only bone injury.